SAT0249 Tocilizumab in the Treatment of Patients with Rheumatoid Arthritis in REAL Clinical Practice: Results of TRUST Study. (10th June 2014) - Gerli, R.; Afeltra, A.; Bagnato, G.; Carlino, G.; Foti, R.; Mazzone, A.; Minisola, G.; Pappone, N.; Russo, R.; Semeraro, A.
Abstract : Background: Tocilizumab (TCZ) is an interleukin-6 receptor inhibitor for treatment of patients (pts) with moderate to severe rheumatoid arthritis (RA) and inadequate response (IR) to disease modifying anti-rheumatic drugs (DMARDs) or anti-Tumor Necrosis Factor (anti-TNF) agents. Objectives: Describe the efficacy and safety of TCZ in pts with RA in Italian clinical practice. Primary endpoint: proportion of pts with remission or low disease activity (LDA) after 6 months of TCZ treatment. Methods: TRUST is a multicenter, retrospective-prospective, observational study in pts with RA who had started treatment with TCZ in the 6 months prior to center opening and were still on treatment at the beginning of the study (retrospective phase); pts were then followed up to a maximum of 12 months after the first TCZ infusion (prospective phase). Results: A total of 322 RA pts were enrolled in 59 Italian centers (mean age: 55.8 years; mean disease duration: 120.5 months; baseline DAS28: 5.3). After 6 months of TCZ treatment, the proportion of pts (57.52%, N=130, p-value<0.0237) achieving LDA (DAS28 ≤3.2) and disease remission (DAS28 ≤2.6; 38.05%, N=86, p-value=0.0003) out of 226 pts with available DAS28 were statistically significant vs baseline. A considerable proportion of pts (32.6%, N=105) was treated in monotherapy with TCZ; clinical benefits are shown in table 1 . No statistically significant differences were found between the two subpopulations of pts: DMARD-IR or TNF-IR in the mean DAS28 and HAQ score from baseline to any post-baseline time point, while a statistically significant difference was found in the mean VAS Fatigue score (48.4 vs. 34.7; p=0.0025) after 6 months of TCZ treatment. 62 pts (19.2%) prematurely discontinued TCZ, 24 for safety reasons. Drug-related adverse events were reported in 28.6% (N=92) of pts (mostly hypercholesterolemia and leucopenia) and serious adverse events in 3.4% (N=11) of patients. Adverse events of special interest were reported in 60 pts (mostly infections). Conclusions: This study confirms the efficacy of TCZ in pts with RA, as it shows a high proportion of patients achieving a low disease activity (57.52%) or disease remission (38.05%) after 6 months of treatment. The clinical benefits of TCZ are also shown in patients treated with TCZ as monotherapy, where DAS28, VAS Fatigue and HAQ scores markedly improved. The low incidence of drug-related adverse events (28.6%) and serious adverse events (3.4%) confirms also the good safety profile of TCZ. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5029